Enhancing bacteriological concept comprehension in multiethnic student through project-based practicum - Didimus Tanah Boleng; Elsje Theodora Maasawet; Hariska Swandana (University of Muhammadiyah Malang, 2024)
The concepts of bacteriology are still poorly understood by students of the Department of Biology Education, Mulawarman University. Certain ethnic characteristics influence student learning processes and outcomes. A quasi-experiment was carried out at the Department of Biology Education, Mulawarman University in the even semester of the 2022/2023 academic year. The aim of the research was to map members of ethnic-based practicum groups in bacteriology practicum in an effort to empower understanding of bacteriology concepts. Ethnic-based practicum means that the practicum is carried out taking into account the ethnic diversity that exists in each group in the class. The research sample was class A and class B students who were taking a bacteriology practicum program. The research instruments were questionnaires and test questions. Data analysis techniques are percentage and covariance analysis. If there is a significant influence, then proceed with Least Significance analysis Difference. The results of data analysis show that there is a significant influence between the application of the product (a Project-Based Learning-based practicum guide) on understanding the concept of bacteriology as a result of development (p˂0.00). The research sample was class A and class B students who were taking a bacteriology practicum program. For further research, practical material needs to be supplemented with other bacteriological materials, and involve more ethnic types.